Measuring redenomination risks in the Euro area: New evidence from survey data - Jens Klose (Philipps-University Marburg, School of Business and Economics, 2019)
This article introduces a new indicator to measure redenomination risks in Euro area countries. The measure is based on survey data. The influence of this indicator in determining sovereign bond yield spreads is tested using an ARDL-approach. The results for ten EMU countries in the period June 2012 to January 2018 show that the risk of a depreciation is almost abandoned for Euro area countries, i.e. the former crisis countries Ireland and Portugal. If anything an appreciation may occur for some countries once they leave the EMU. The only countries facing depreciation problems once leaving the monetary union are Italy and to some extent Spain.
Keywords: E43; F45; G01; 330; Redenomination Risk; Euro Area; Exit